Di rin magbabago ang damdamin the UP Men's Basketball Team stakeholders' lived experience of rooting for the underdog - Enriquez, Francine Joy M.; Yenko, Rane Astrid M.
The unwavering loyalty of UP Men's Basketball Team (UPMBT) stakeholders, even as the team transitions from underdog to championship contender status, presents a curious case for understanding the culture and psychology involved in long-term sports support in the Philippines. As the country faces structural and financial challenges that hinder sports development in regions like Central Luzon, this study investigates how sustained stakeholder commitment is nurtured to inspire sports communities and models of engagement. to explore the phenomena of long-term stakeholder support for underdog teams, 17 long-term supporters of the UPMBT or those present before Season 77 of the UAAP, were sampled and invited for semi-structured interviews regarding their personal experiences in supporting the team. Through thematic analysis, themes surrounding motivation, nature of support, significance, roles, vision, and culture building were identified. The phenomena of stakeholder support suring an Underdog Era is driven not by performance, but by emotional connections that positioned the team as a symbol of values and community. It emphasizes the importance of relationship-based and values-driven approaches to sustaining sports engagement especially in developing varsity teams and communities like that of Central Luzon's. By building a foundation of cultural and emotional bond over outcome, teams, sponsors, and institutions can build long-term stakeholder loyalty. Through practical applications of policy, programs and sports psychology, and community-wide engagement sampled by the UPMBT, a grounded sports community in the Philippines may flourish.